Application of Stem Cell-Derived Extracellular Vesicles as an Innovative Theranostics in Microbial Diseases - Keshavarz Alikhani, Hani; Shokoohian, Bahare; Rezasoltani, Sama; Hossein-khannazer, Nikoo; Yadegar, Abbas; Hassan, Moustapha; Vosough, Massoud (Frontiers in Microbiology, 2021)
Extracellular vesicles (EVs), as nano-/micro-scale vehicles, are membranous particles containing various cargoes including peptides, proteins, different types of RNAs, and other nucleic acids, and lipids. These vesicles are produced by all cell types, in which stem cells are a potent source for them. Stem cell-derived EVs could be promising platforms for treatment of infectious diseases and early diagnosis. Infectious diseases are responsible for more than 11 million deaths annually. Highly transmissible nature of some microbes, such as newly-emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), drives researcher’s interest to set up different strategies to develop novel therapeutic strategies. Recently, EVs-based diagnostic and therapeutic approaches have been launched and gaining momentum very fast. The efficiency of stem cell-derived EVs on treatment of clinical complications of different viruses and bacteria, such as SARS-CoV-2, hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), Staphylococcus aureus, Escherichia coli has been demonstrated. On the other hand, microbial pathogens are able to incorporate their components into their EVs. The microbe-derived EVs have different physiological and pathological impacts on the other organisms. In this review, we briefly discussed biogenesis and the fate of EVs. Then, EV-based therapy was described and recent developments in understanding the potential application of stem cell-derived EVs on pathogenic microorganisms were recapitulated. Furthermore, the mechanisms by which EVs were exploited to fight against infectious diseases were highlighted. Finally, the deriver challenges in translation of stem cell-derived EVs into the clinical arena were explored.